Amyloid Accumulation in the Toxic Nodule of the Thyroid Gland in a Patient with End Stage Renal Failure - Umut Mousa; Sema Aktas; Halit Uner (Case Reports in Endocrinology)
Amyloidosis is characterized by accumulation of amorphous, proteinaceous material in various organs and tissues of the body. Amyloid may accumulate in the thyroid gland in cases of medullary thyroid carcinoma and systemic amyloidosis. Amyloid accumulates extracellularly in the thyroid parenchyma and disrupts the normal follicular patterns. Most of the cases reported up to now were clinically euthyroid, but many presentation forms and overlaps have been reported. Herein we present a patient with toxic nodular goiter with amyloid deposition in the toxic nodule as well as the remaining thyroid tissue.